2015
DOI: 10.1093/mnras/stv2165
|View full text |Cite
|
Sign up to set email alerts
|

The impact of baryonic physics on the structure of dark matter haloes: the view from the FIRE cosmological simulations

Abstract: We study the distribution of cold dark matter (CDM) in cosmological simulations from the FIRE (Feedback In Realistic Environments) project, for M * ∼ 10 4−11 M galaxies in M h ∼ 10 9−12 M halos. FIRE incorporates explicit stellar feedback in the multi-phase ISM, with energetics from stellar population models. We find that stellar feedback, without "fine-tuned" parameters, greatly alleviates small-scale problems in CDM. Feedback causes bursts of star formation and outflows, altering the DM distribution. As a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
409
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(446 citation statements)
references
References 135 publications
(220 reference statements)
35
409
2
Order By: Relevance
“…1 and its scatter. The parameters of the fitting are reported in Table 3. A similar agreement is also found when comparing our rusults with recent simulations presented by the FIRE collaboration in Chan et al (2015). For example there is a quite remarkable similarity in the peak of the core formation and in the non monotonic response of DM to galaxy formation.…”
Section: Resultssupporting
confidence: 91%
“…1 and its scatter. The parameters of the fitting are reported in Table 3. A similar agreement is also found when comparing our rusults with recent simulations presented by the FIRE collaboration in Chan et al (2015). For example there is a quite remarkable similarity in the peak of the core formation and in the non monotonic response of DM to galaxy formation.…”
Section: Resultssupporting
confidence: 91%
“…They found a non-linear dependence between the inner slope and stellar to halo mass. This result has been confirmed with a larger sample of galaxies from NIHAO (Tollet et al 2016), and a small sample of higher resolution galaxies from FIRE (Chan et al 2015). Since we use the same simulations our results are consistent with Di Cintio et al (2014a) and Tollet et al (2016).…”
Section: Comparison To Previous Resultssupporting
confidence: 89%
“…A lower threshold is expected to result in a more uniform star formation history, with fewer starbursts, and hence fewer outflow events with high fout, and thus weaker expansion. However, Dutton et al (2015) found halo expansion that follows the NIHAO results in the progenitors of massive elliptical galaxies using a threshold of n th ∼ 1 cm −3 , and the FIRE simulations (Chan et al 2015) are also consistent with NIHAO (from dwarfs to MW mass haloes) and use a higher threshold of n th > 10 − 100 cm −3 . Thus the halo response does not seem strongly sensitive to the star formation threshold, at least for n th > 1 cm −3 .…”
Section: Comparison To Previous Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Table 1 describes the simulations used in this paper. Our sample includes most of the initial FIRE runs (Hopkins et al 2014) (m09, m10, m11, m12i, m12q, m12v), as well as the z2h runs first introduced in Faucher-Giguère et al (2015) which simulate lowmass Lyman-break galaxies to z = 2, four additional dwarf galaxies run to z = 0 first presented in Chan et al (2015) (m10h1297, m10h1146, m10h573, and m11h383) , and two additional L*-like galaxies (m11.4a and m11.9a) presented in Hafen et al (2016). In this work, we primarily consider the central, most massive galaxy in each simulation, though we use additional galaxies that meet inclusion criteria in Section 3.1.…”
Section: Simulationsmentioning
confidence: 99%